Pengaturan Pedoman Pemidanaan KUHP Baru dan Implikasinya pada Putusan Hakim - Latifah, Marfuatul; Hairi, Prianter Jaya (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2024)
The enactment of Law No. 1 of 2023 on the Criminal Code replaces the old Dutch colonial Criminal Code (Wetboek van Strafrecht). One of the key provisions in the new Criminal Code is the regulation of sentencing guidelines. This article, which is based on normative legal research, aims to explore the concept of sentencing guidelines in the new Criminal Code and their implications for future sentencing decisions. The article finds that the sentencing guidelines outlined in the new Criminal Code serve as a framework for judges to ensure that their decisions meet the standards of justice, utility, and the objectives of sentencing, which include prevention, rehabilitation, and the restoration of balance following criminal acts. Moreover, these guidelines provide a means to balance judicial independence with legal consistency, thereby reinforcing public trust in Indonesia’s judicial system. The article concludes that the sentencing guidelines in the new Criminal Code can act as an instrument to ensure that sentencing decisions meet societal expectations of justice and utility while fulfilling the broader objectives of sentencing. The guidelines encompass provisions for natural persons and corporations, as well as considerations for aggravating circumstances and other relevant factors. The article recommends increasing the dissemination of these sentencing guidelines to law enforcement officials, improving the quality of judges, and finalizing government regulations to provide further technical provisions for their implementation. AbstrakPengesahan UU No. 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana menggantikan KUHP lama warisan kolonial belanda (wetboek van strafrecht). Salah satu substansi terpenting dari KUHP baru ialah pengaturan pedoman pemidanaan. Artikel ini termasuk jenis penelitian hukum normatif yang bertujuan untuk mengkaji bagaimana konsep pedoman pemidanaan dalam KUHP baru dan implikasinya bagi putusan pemidanaan di masa mendatang. Artikel ini menemukan bahwa pedoman pemidanaan yang dituangkan dalam KUHP baru berfungsi sebagai panduan bagi hakim untuk memastikan putusan yang diambil memenuhi standar keadilan, kemanfaatan, serta tujuan pemidanaan yang meliputi pencegahan, pembinaan, dan pemulihan keseimbangan akibat tindak pidana. Selain itu pedoman pemidanaan ini dapat menjadi alat penjaga keseimbangan antara kebebasan hakim dan konsistensi hukum, sehingga menjaga kepercayaan publik terhadap sistem peradilan di Indonesia. Artikel ini menyimpulkan bahwa Pengaturan pedoman pemidanaan dalam KUHP baru, dapat menjadi instrumen untuk memastikan bahwa putusan yang diambil memenuhi standar keadilan dan kemanfaatan yang diharapkan oleh masyarakat dan memenuhi tujuan pemidanaan karena memuat berbagai ketentuan terkait pedoman pemidanaan secara umum, bagi pelaku pidana orang natural, bagi korporasi, alasan pemberat, dan ketentuan lainnya. Artikel ini menyarankan peningkatan sosialisasi pedoman pemindanaan bagi aparat penegak hukum, peningkatan kualitas hakim, dan penyelesaian peraturan pemerintah sebagai ketentuan teknis lebih lanjut dari pedoman pemidanaan ini.